THE HUMOROUS EFFECTS IN POLITICAL DISCOURSE DURING INTERVIEWS: RHETORIC, PERFORMANCE, AND DEMOCRATIC AMBIVALENCE IN THE CASE OF DONALD TRUMP’S 2025 SPEECH - Azimova Marjona Salim qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  develops  a  theoretically  grounded  and  discourse-analytical  account of  humor  in  contemporary  political  interviews, situating  Donald Trump’s 2025 interview speech within broader transformations of mediated political communication.  Drawing  on  classical  rhetoric,  Bakhtinian  carnivalesque  theory, psychoanalytic  relief  theory,  and  Goffman’s  dramaturgical  sociology,  the  paper conceptualizes political humor as a multifunctional discursive mechanism operating at the  intersection  of  persuasion,  identity  construction,  affect  regulation,  and accountability  management.  Through  comparative  analysis  with  interview performances  by  Barack  Obama  and  Volodymyr  Zelenskyy,  the  study  proposes  a typology of dominance, self-reflexive, and solidaristic humor. It argues that humor in political interviews constitutes a form of “affective governance” that simultaneously intensifies political engagement and destabilizes deliberative norms.